Declaration de la volonte du roy addressee a nosseigneurs de sa cour de Parlement. - France. (Declaration de la volonte dv roy addressee a nosseignevrs de sa cour de Parlement, 1615)
"The King here discusses his journey to Bordeaux for the purpose of his approaching marriage with the Spanish Infanta. He is worried that the rebelling Princes will impede his journey to Bordeaux. He wishes as many of the Nobles as can to accompany him, both for protection as well as for providing a retinue at this once in a life time occasion"--French Political Pamphlets Digital Collection, Brigham Young University.
"Donné à Paris le trentiesme iuillet mil cens quinze. Signé Louys & plus bas de Lomenie"--Page 8
Lindsay, R.O. French political pamphlets, 1547-1648,entry 3389
"The King here discusses his journey to Bordeaux for the purpose of his approaching marriage with the Spanish Infanta. He is worried that the rebelling Princes will impede his journey to Bordeaux. He wishes as many of the Nobles as can to accompany him, both for protection as well as for providing a retinue at this once in a life time occasion"--French Political Pamphlets Digital Collection, Brigham Young University.
Also available via the World Wide Web.
RBC copy: Disbound.
Keywords: Politics and government. / fast / https://id.worldcat.org/fast/1919741; France. / fast / https://id.worldcat.org/fast/1204289; France / History / Louis XIII, 1610-1643 / https://id.loc.gov/authorities/subjects/sh85051303 / Pamphlets. / https://id.loc.gov/authorities/subjects/sh99001703; France / Politics and government / 1610-1643 / https://id.loc.gov/authorities/subjects/sh85051466; Pamphlets / https://vocab.getty.edu/aat/300220572 / France / Paris / https://id.loc.gov/authorities/names/n79058874-781 / Seventeenth century (dates CE). / https://vocab.getty.edu/aat/300404511 / aat